Impact of Television Advertisements on the Lifestyles of Urban Youth in Kathmandu - Gopal Thapa (Pravaha, 2023)
The study's objective was to examine the impact of television advertisements on the lifestyle of urban Nepalese youth based on attitudes, tastes, habits, and moral standards. It also tried to measure the usefulness of ads in changing the urban youth lifestyle and its impact on Nepalese urban youth. This study was mainly an urban-educated youth-based analytical study, undertaken in Kathmandu Valley based on 200 respondents as sample sizes which were taken part in the survey, out of which 80 were male and 120 were female. The study relied on primary data collected from various colleges at Tribhuvan University. In the study, most respondents agreed that the television advertisement has changed the lifestyle of urban youths.